PSYCHOLOGY OF LEARNING AS THE MAIN PILLAR OF EDUCATION: CONCEPTS, FUNCTIONS AND APPLICATIONS - Pujiati, Pujiati; Afandi, Muslim; Subhan, MHD (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Contemporary education is faced with the challenge of meeting the diverse learning needs of students, thus requiring an approach that goes beyond mere knowledge transfer. The failure of the ‘one-size-fits-all’ teaching model emphasizes the urgency of a deep understanding of how individuals learn, of which learning psychology serves as a fundamental pillar. Based on this, this study aims to conduct a comprehensive literature review to synthesize the core principles of learning psychology and formulate their practical implications in effective instructional design. This study uses a qualitative literature study method, with secondary data collection from credible academic sources such as books, scientific articles, and journals through digital databases. The selection of literature is based on relevance and content validity. The results of the synthesis show that major theories such as behaviorism, cognitivism, and constructivism convergently emphasize the importance of feedback, active student engagement, and metacognitive processes. Furthermore, the literature consistently emphasizes its crucial role in diagnosing learning difficulties and designing differentiated instruction. It is concluded that mastery of learning psychology is an essential foundation for educators to transform towards a student-centered paradigm, creating an adaptive, inclusive learning environment that is able to develop students’ potential holistically. ABSTRAK Pendidikan kontemporer dihadapkan pada tantangan untuk memenuhi kebutuhan belajar siswa yang beragam, sehingga menuntut pendekatan yang lebih dari sekadar transfer pengetahuan. Kegagalan model pengajaran 'satu untuk semua' menekankan urgensi pemahaman mendalam tentang bagaimana individu belajar, di mana psikologi pembelajaran berfungsi sebagai pilar fundamentalnya. Berdasarkan hal tersebut, penelitian ini bertujuan untuk melakukan tinjauan literatur komprehensif guna mensintesis prinsip-prinsip inti psikologi pembelajaran dan merumuskan implikasi praktisnya dalam desain instruksional yang efektif. Penelitian ini menggunakan metode studi literatur kualitatif, dengan pengumpulan data sekunder dari sumber akademis kredibel seperti buku, artikel ilmiah, dan jurnal melalui basis data digital. Seleksi literatur didasarkan pada relevansi dan validitas konten. Hasil sintesis menunjukkan bahwa teori-teori utama seperti behaviorisme, kognitivisme, dan konstruktivisme secara konvergen menekankan pentingnya umpan balik, keterlibatan aktif siswa, dan proses metakognitif. Lebih lanjut, literatur secara konsisten menegaskan peran krusialnya dalam mendiagnosis kesulitan belajar dan merancang instruksi terdiferensiasi. Disimpulkan bahwa penguasaan psikologi pembelajaran adalah fondasi esensial bagi pendidik untuk bertransformasi menuju paradigma yang berpusat pada siswa, menciptakan lingkungan belajar yang adaptif, inklusif, dan mampu mengembangkan potensi siswa secara holistik.